CERTAINTY OF MEDICAL PRACTICE LICENSES PLATFORM TELEMEDICINE FROM A HEALTH LAW PERSPECTIVE AS A FORM OF COMMUNITY PROTECTION IN INDONESIA - Nugroho Iman Wibisono; Endeh Suhartini; Ani Yumarni (Law Studies and Justice Journal (LAJU), 2025)
The development of telemedicine as a form of digital transformation in the healthcare sector has emerged as an alternative solution to the uneven distribution of healthcare workers and medical facilities, particularly in underdeveloped, frontier, and outermost (3T) areas. While telemedicine expands public access to medical services, it also raises legal issues, particularly regarding the legitimacy of medical practice on online platforms. To date, there are no specific regulations governing the ownership of a Practice License (SIP) for telemedicine services. This regulatory gap creates potential legal uncertainty, weakens patient protection, and increases the vulnerability of healthcare workers to civil and criminal prosecution. This study aims to analyze the form of government oversight of telemedicine practices in Indonesia based on the Health Law, emphasizing efforts to prevent potential malpractice and guarantee legal protection for medical personnel as well as the public's constitutional rights to health services through the issuance of a License for Telemedicine Services (SIP). This study uses a normative-sociological juridical approach, which examines law from three dimensions: legal text, legal values, and social reality. The research findings indicate that SIP not only serves as an administrative instrument for legitimizing medical practice, but also as a manifestation of the state's responsibility to ensure professional competence, accountability, and legal protection for medical personnel in online therapeutic interactions with patients. Without adaptive SIP regulations, the state risks failing to fulfill its constitutional mandate to provide fair, equitable, and quality healthcare services. Therefore, SIP regulations compatible with the telemedicine ecosystem are a necessity in the era of increasingly decentralized digital healthcare.